Cell Line-Dependent Variability of Coordinate Expression of p75NTR and CRABP1 and Modulation of Effects of Fenretinide on Neuroblastoma Cells. (30th December 2015) - Yang, Yaoli Pu; Wang, Simeng; Li, Xingguo; Schor, Nina F.
Abstract : Neuroblastoma is a childhood neural crest tumor. Fenretinide, a retinoic acid analogue, induces accumulation of mitochondrial reactive oxygen species and consequent apoptosis in neuroblastoma cells. The p75 neurotrophin receptor (p75NTR) enhances the antineuroblastoma cell efficacy of fenretinide in vitro . We examined the role of the retinoid binding protein, CRABP1, in p75NTR-mediated potentiation of the efficacy of fenretinide. Knockdown and overexpression, respectively, of either p75NTR or CRABP1 were effected in neuroblastoma cell lines using standard techniques. Expression was determined by qRT-PCR and confirmed at the protein level by Western blot. Metabolic viability was determined by Alamar blue assay. While protein content of CRABP1 correlated roughly with that of p75NTR in the three neuroblastoid or epithelioid human neuroblastoma cell lines studied, manipulation of p75NTR expression resulted in cell line-dependent, variable change in CRABP1 expression. Furthermore, in some cell lines, induced expression of CRABP1 in the absence of p75NTR did not alter cell sensitivity to fenretinide treatment. The effects of manipulation of p75NTR expression on CRABP1 expression and the effects of CRABP1 expression on fenretinide efficacy are therefore neuroblastoma cell line-dependent. Potentiation of the antineuroblastoma cell effects of fenretinide by p75NTR is not mediated solely through CRABP1.